Clinical features of LRP4/agrin‐antibody–positive myasthenia gravis: A multicenter study. Issue 3 (10th June 2020) - Rivner, Michael H.; Quarles, Brandy M.; Pan, Jin‐Xiu; Yu, Zheng; Howard, James F.; Corse, Andrea; Dimachkie, Mazen M.; Jackson, Carlayne; Vu, Tuan; Small, George; Lisak, Robert P.; Belsh, Jerry; et al.
Abstract: Introduction: Our aim in this study was to identify the prevalence and clinical characteristics of LRP4/agrin‐antibody–positive double‐seronegative myasthenia gravis (DNMG). Methods: DNMG patients at 16 sites in the United States were tested for LRP4 and agrin antibodies, and the clinical data were collected. Results: Of 181 DNMG patients, 27 (14.9%) were positive for either low‐density lipoprotein receptor–related protein 4 (LRP4) or agrin antibodies. Twenty‐three DNMG patients (12.7%) were positive for both antibodies. More antibody‐positive patients presented with generalized symptoms (69%) compared with antibody‐negative patients (43%) ( P ≤ .02). Antibody‐positive patients' maximum classification on the Myasthenia Gravis Foundation of America (MGFA) scale was significantly higher than that for antibody‐negative patients ( P ≤ .005). Seventy percent of antibody‐positive patients were classified as MGFA class III, IV, or V compared with 39% of antibody‐negative patients. Most LRP4‐ and agrin‐antibody–positive patients (24 of 27, 89%) developed generalized myathenia gravis (MG), but with standard MG treatment 81.5% (22 of 27) improved to MGFA class I or II during a mean follow‐up of 11 years. Discussion: Antibody‐positive patients had more severe clinical disease than antibody‐negative patients. Most DNMG patients responded to standard therapy regardless of antibody status.